The Position of Maxilla in Class III Patients - Gökmen Kurt; Ayşe Tuba Altuğ Ataç; Öykü Nebioğlu-Dalcı (Galenos Yayinevi, 2007)
The purpose of the study was to identify the maxillary growth trend of the skeletal Class III individuals with and without openbite, and to define if the growth of the maxilla is effected by the position of the mandible. The patients included in the study were divided into three groups. The first group consisted of individuals (female: 8, male: 6, total: 14; mean age 14.3 years) with skeletal Class III + open-bite, the second group consisted of individuals (female: 7, male: 7, total: 14; mean age 13.8 years) with skeletal Class III without openbite and the third group, which acted as the control group consisted of individuals (female: 12, male: 5, total: 17; mean age 13.1 years) with skeletal Class I relationship. The measurements were done on pre-treatment/pre-control lateral cephalometric radiographs. In the study, the descriptive measurements (SNA, SNB, ANB, overjet, overbite, SN/Go-Gn, ANS-Me), measurements that define the size and position of the maxilla (A-VR, Co-A, ANS-PNS, Nperp-A) and the mandible (B-VR, Pg-VR, S-Go, Co-Go, Co-Gn, Go-Gn, Nperp-Pg) were evaluated. The differences between the groups were determined by Analysis of Variance and Duncan's tests. There were statistically significant differences between the two skeletal Class III groups in B-VR (p<0.05), ANS-Me, overjet and overbite (p<0.01). The parameters related with the growth of the maxilla were similar in both groups. The skeletal and positional structure of the maxilla in Class III individuals happen to be hardly influenced by the restriction of the mandibular incisors and negative overjet.